Micronutrient antioxidant supplementation alleviates valproic acid-induced oxidative stress and male infertility via the NRF2/HO-1 pathway - Muhammad Arif Asghar; Bing Wan; Lu Li; Jie Zhang; Shixin Tang; Hang Han; Yuanyuan Yang; Long Chu; Qian Zhang; Xiao Zhang; Qinjian Zhao (Redox Biology)
Background: Valproic Acid (VPA), a widely used anticonvulsant, is known to induce oxidative stress, contributing to male infertility. This study explores the potential of micronutrient antioxidants to improve fertility in VPA-treated individuals. Methods: Six-week-old male mice were treated with VPA and supplemented with antioxidants, including l-Arginine (120 mg/kg), N-Acetylcysteine (NAC) (2 mg/kg), Taurine (200 mg/kg), L-Tryptophan (0.5 mg/kg), Zinc chloride (ZnCl2) (1.5 mg/kg), and Selenium (0.5 mg/kg). The dosing regimen lasted for 34 days. Sperm quality, oxidative stress, and inflammatory biomarkers were assessed through gene expression analysis, western blotting, histological assessments, TUNEL assays, and immunohistochemistry. Additionally, GC-2spd(ts) and HepG2 cell lines were used to examine the testicular and systemic effects of VPA and antioxidants. Network pharmacology was applied to identify key molecular targets and pathways. Results: Antioxidant supplementation significantly improved sperm count, with l-Arginine showing an approximately 296.1 % increase, NAC a 270.7 % increase, and Taurine a 255.9 % increase compared to the VPA-only group. Furthermore, antioxidants enhanced semen volume, testosterone levels, sperm motility, morphology, and viability. Gene expression analysis revealed significant upregulation of key oxidative stress-related proteins such as SOD1, HO-1, NRF2, and NQO1. Western blot and histological analyses showed a reversal of oxidative stress and preservation of seminiferous tubule integrity. TUNEL assays demonstrated a reduction in apoptotic damage, and IHC confirmed an increase in HO-1 and SOD1. In vitro studies with GC-2spd(ts) and HepG2 cells confirmed that antioxidants alleviated VPA-induced oxidative stress. Network pharmacology identified key molecular targets, such as GPX4, SOD1, HO-1, and NRF2, which are involved in oxidative stress, apoptosis, and inflammation pathways, that were modulated by antioxidants. Conclusion: Micronutrient antioxidants effectively reduce VPA-induced oxidative stress and improve male fertility. These results suggest that antioxidant supplementation could be a promising strategy to mitigate oxidative damage and enhance fertility in individuals undergoing VPA therapy.